DRIVERS OF GREEN INVESTMENT THROUGH A THEORY OF PLANNED BEHAVIOR - Rahmamita, Deane; Hizryan, Fikri (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Climate change has prompted global attention to sustainable finance, which aims to support economic growth in line with social and environmental aspects. Indonesia's Financial Services Authority (OJK) has implemented a sustainable finance roadmap since 2014, focusing on green investments that support environmentally friendly practices in business. Based on data from Kustodian Sentral Efek Indonesia (KSEI), in January 2025 Indonesia had reached 15.5 million capital market investors, 99.7% of whom were retail investors, with the majority concentrated in DKI Jakarta. To understand this phenomenon, this study aims to identify the factors that influence Indonesian investors' green investment behavior, particularly in DKI Jakarta and West Java provinces as the largest population in Indonesia using Theory of Planned Behavior framework. This study is a quantitative study using primary data obtained from a questionnaire distributed to investors in DKI Jakarta and West Java Province via social media. Data analysis uses PLS-SEM. The results indicate that attitude and perceived behavioral control significantly influence intention towards green investment which in turn positively impact investment behavior. In contrast, subjective norm does not have a significant effect on intention towards green investment. These findings imply that strategies to promote green investment should prioritize enhancing positive attitudes and strengthening individuals perceived control over investment decisions.